A comparative study of different calculating methods of glomerular filtration rate for evaluating GFR in patients with chronic kidney disease - CHAI Li-chao; WANG Jing; WEI Yan; LIU Chun-na; ZHANG Yu-jiao; XIA Han (Linchuang shenzangbing zazhi)
Objective To explore the effects of modified 99 mTc-DTPA Gates formula, 99 mTc-DTPA Gates method and CKD-EPIcr/cysc（2012） formula for evaluating glomerular filtration rate（GFR） in patients with chronic kidney disease（CKD）. Methods A total of 180 patients diagnosed with CKD were used as the study subject to undergo examinations of examined by double plasma method and renal dynamic imaging. The modified formula of 99 mTc-DTPA Gates method and 99 mTc-DTPA Gates method were used to calculate gGFR and pGFR, and the formula of CKD-EPIcr/cysc（2012） was used to calculate eGFR. The bias, accuracy and 95% consistency of the Gates method（gGFR） and the two formulas were compared by using the tGFR values determined by double plasma assay as the gold standard. Results The positive correlation coefficients of pGFR, eGFR,gGFR with tGFR were r=0.83, 0.76 and 0.69, respectively. The median bias, absolute value and accuracy of pGFR, eGFR and gGFR from tGFR decreased significantly in turn（P<0.05）. Conclusions Compared with CKD-EPIcr/cysc（2012） formula and 99 mTc-DTPA Gates method, the modified formula of 99 mTc-DTPA Gates method has less bias, better accuracy for evaluating CKD patients, and should be popularized in clinical practice.